Principals’ managerial factors and teachers’ job effectiveness in public senior secondary schools - Adeseko Sunday Olaifa; Solawat Ajibola Hassan; Simbiat Mojibola Fagbola; Oba Baba Ayoku; Taibat Joke Abolarin (Inovasi Kurikulum, 2024)
The study examined principals’ managerial factors and teachers’ job effectiveness in public senior secondary schools in Ilorin Metropolis, Kwara State. The objectives of the study were to examine the managerial factors of principals in public senior secondary schools in Ilorin Metropolis, Kwara State; determine the level of teachers’ job effectiveness in public senior secondary schools in Ilorin Metropolis, Kwara State; and investigate the relationship between principals’ managerial factors and teachers’ job effectiveness in public senior secondary schools in Ilorin Metropolis, Kwara State. The Research Advisor's sample size determination was used to select 317 respondents. Principals’ Managerial Factors and Teachers’ Job Effectiveness Questionnaire were used to collect the data for this study. Findings indicated a significant relationship between principals’ managerial factors and teachers’ job effectiveness in public senior secondary schools in Ilorin Metropolis, Kwara State. There was a significant relationship between principals’ communication skills, principals’ supervisory skills, principals’ record-keeping skills, and principals’ interpersonal relationship skills, and teachers’ job effectiveness in public senior secondary schools in Ilorin Metropolis, Kwara State. It was recommended, among others, that school principals improve their communication skills by adopting different means of communication to ensure every teacher does his or her teaching job well. AbstrakStudi ini menguji faktor manajerial kepala sekolah dan efektivitas kerja guru di sekolah menengah atas negeri di Ilorin Metropolis, Negara Bagian Kwara. Tujuan dari penelitian ini adalah untuk menguji faktor manajerial kepala sekolah di sekolah menengah atas negeri di Ilorin Metropolis, Negara Bagian Kwara; menentukan tingkat efektivitas kerja guru di sekolah menengah atas negeri di Ilorin Metropolis, Negara Bagian Kwara dan menyelidiki hubungan antara faktor manajerial kepala sekolah dan efektivitas kerja guru di sekolah menengah atas negeri di Ilorin Metropolis, Negara Bagian Kwara. Penentuan ukuran sampel Research Advisors digunakan untuk memilih 317 responden. Faktor Manajerial Kepala Sekolah dan Kuesioner Efektivitas Kerja Guru digunakan untuk mengumpulkan data dalam penelitian ini. Temuan menunjukkan bahwa terdapat hubungan yang signifikan antara faktor manajerial kepala sekolah dan efektivitas kerja guru di sekolah menengah atas negeri di Ilorin Metropolis, Negara Bagian Kwara. Terdapat hubungan yang signifikan antara keterampilan komunikasi kepala sekolah, keterampilan pengawasan kepala sekolah, keterampilan pencatatan kepala sekolah dan keterampilan hubungan interpersonal kepala sekolah dengan efektivitas kerja guru di sekolah menengah atas negeri di Ilorin Metropolis, Negara Bagian Kwara. Direkomendasikan antara lain; kepala sekolah harus berupaya meningkatkan keterampilan komunikasi mereka dengan menggunakan cara komunikasi yang berbeda untuk memastikan setiap guru melakukan pekerjaan mengajarnya dengan baik.Kata Kunci: efektivitas kinerja guru; faktor manajerial kepala sekolah; keterampilan komunikasi